ANALISIS PENILAIAN TINGKAT KESEHATAN BANK SYARIAH BERDASARKAN METODE RGEC TAHUN 2012 - 2016 - KHUDORI, AHMAD (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2018)
The purpose of this research is to know the level of health of Islamic banking in Indonesia using RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) in the period 2012 – 2016. Research methods used include quantitative and qualitative methods. On quantitative method describes the Risk Profile using NPF financial ratios (Non Performing Financing), and FDR (Financing the Deposit Ratio), using Earnings ratio ROA (return on assets), ROE (return on equity), BOPO (Cost to Income Ratio), and Capital used CAR (Capital Adequacy Ratio). On the qualitative method describes the Good Corporate Governance. Types of data used are secondary data in the form of annual reports and publications reports published on the website that is managed per Islamic banking in Indonesia. The results of the research show that there are some health conditions in Islamic banking by category very healthy is Panin Bank Syariah, healthy category i.e, BCA Bank Syariah, BNI Bank Syariah, BRI Bank Syariah, Bukopin Bank, Mandiri Bank Syariah, Mega Bank Syariah, Muamalat Bank Syariah, and Victoria Bank Syariah. Categories less healthy are MayBank Syariah.